2022
DOI: 10.33448/rsd-v11i10.32583
|View full text |Cite
|
Sign up to set email alerts
|

Fungal amylases applied to the sweet potato starch for bioethanol production

Abstract: Bioethanol is a sustainable energy source to help reducing the emission of pollutants into the global environment. In order to cope with that, the ethanol production technologies and use of efficient and low-cost substrates are developed. The objective of this research was to evaluate fungal amylases in sweet potato starch for bioethanol production by Saccharomyces cerevisiae in the laboratory. Endomelanconiopsis endophytica (1.40 U/mL), Neopestalotiopsis cubana (1.67 U/mL) and Fusarium pseudocircinatum (1.11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Recently, Romão et al (2022) reported the production of amylases by E. endophytica isolated from the digestive tract of Phylloicus sp. The authors verified that the amylases were moderately tolerant to temperature variations and poorly tolerant to pH variations, when the fungus was cultivated in sweet potato starch.…”
Section: Molecular Identification Of Endophytic Fungi Qat_7ac From An...mentioning
confidence: 99%
“…Recently, Romão et al (2022) reported the production of amylases by E. endophytica isolated from the digestive tract of Phylloicus sp. The authors verified that the amylases were moderately tolerant to temperature variations and poorly tolerant to pH variations, when the fungus was cultivated in sweet potato starch.…”
Section: Molecular Identification Of Endophytic Fungi Qat_7ac From An...mentioning
confidence: 99%